2016
DOI: 10.1016/j.physe.2015.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Curvature-induced bound states and coherent electron transport on the surface of a truncated cone

Abstract: We study the curvature-induced bound states and the coherent transport properties for a particle constrained to move on a truncated cone-like surface. With longitudinal hard wall boundary condition, the probability densities and spectra energy shifts are calculated, and are found to be obviously affected by the surface curvature. The bound-state energy levels and energy differences decrease as increasing the vertex angle or the ratio of axial length to bottom radius of the truncated cone. In a two-dimensional … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Later on, an approach which does not suffer from this ambiguity was devised by Jensen and Koppe [4] in the 1970s and by Da Costa [5,6] in the 1980s, showing that a geometry-induced potential (GIP) acts upon the dynamics 1 . Since then, some research on the subject has been reported, such as a path integral formulation [13,14], effects on the eigenstates of nanostructures [15,16], interaction with an electromagnetic potential [17,18,19,20], modeling of bound states on conical surfaces [21,22,23], spinorbit interaction [24,25,26], electronic transport in nanotubes [27,28], and bent waveguides [11,29,30,31], just to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…Later on, an approach which does not suffer from this ambiguity was devised by Jensen and Koppe [4] in the 1970s and by Da Costa [5,6] in the 1980s, showing that a geometry-induced potential (GIP) acts upon the dynamics 1 . Since then, some research on the subject has been reported, such as a path integral formulation [13,14], effects on the eigenstates of nanostructures [15,16], interaction with an electromagnetic potential [17,18,19,20], modeling of bound states on conical surfaces [21,22,23], spinorbit interaction [24,25,26], electronic transport in nanotubes [27,28], and bent waveguides [11,29,30,31], just to name a few.…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, the commutators [pi,pj] turn out to satisfy the following relation with f,kf/xk, false[pi,pjfalse]=i2(njni,lninj,l)pl+pl(njni,lninj,l),and the Hamiltonian operator turns out to be, H=p22μ28μM2+VG.The second and key finding of this Letter is: With the quantum condition being imposed, the curvature‐induced potential VG proves to be the geometric potential what has been expected for more than three and a half decades. Being KNn:Nn=(ni,j)2 in fact the trace of square of the extrinsic curvature tensor, the geometric potential is VG=24μK+28μM2…”
Section: Dirac Brackets and Quantization Conditionsmentioning
confidence: 99%
“…This CPF has a distinct feature for no presence of any ambiguity. It is thus a powerful tool to examine various curvature‐induced consequences in two‐dimensional curved surfaces or curved wires . Experimental confirmations of the geometric potential include: an optical realization in 2010 and an observation of its effects in an uneven periodic caged peanut‐shaped nanostructure in 2012 .…”
Section: Introductionmentioning
confidence: 99%
“…Quantum transmission is a natural property of nanostructure devices, in which the topological effect is considerable. Recently, the geometric effects on the coherent electron transport have been investigated in bent cylindrical surfaces [28], and in the surface of a truncated cone [29]. Additionally, the curvature effects on vitrification behavior has been discussed for polymer nanotubes [30].…”
Section: Introductionmentioning
confidence: 99%